When Simplification Leads to Ambiguity: A Look at Two Ocean Metrics for the Subpolar North Atlantic - Léon Chafik; M. Susan Lozier (Geophysical Research Letters)
Abstract The AMOC FINGERPRINT and GYRE INDEX are two widely used metrics by the oceanographic community to assess whether northward ocean heat transport, and consequently temperature variability in the subpolar North Atlantic, is primarily governed by the Atlantic overturning circulation or the horizontal gyre circulation. Although these metrics are presented as distinct measures of subpolar ocean circulation, we contend that they are not unique indicators of the dynamics they are intended to represent. Instead, our analysis demonstrates that both metrics are essentially capturing variability in upper ocean heat content, which can result from a number of mechanisms. This conclusion, corroborated with direct overturning measurements from the OSNAP and RAPID programs, raises concerns about the use of these metrics to infer the dynamics responsible for past and projected changes in subpolar ocean temperatures.